PRELIMINARY EVALUATION OF THE WOUND HEALING EFFECT OF VITEX DONIANA SWEET (VERBENACEAE) IN MICE. - Amegbor, kossi; Metowogo, Koffi; Eklu-Gadegbeku, Kwashi; Agbonon, Amegnona; Aklikokou, Kodjo Amedonou; Napo-koura, Gado; Gbeassor, Messanvi (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Vitex doniana is traditionally used in Togo to treat various diseases including wounds. The aim of this work was to evaluate the efficiency of Vitex doniana on cutaneous wound healing. Wounds were induced in ICR mice divided into four groups as following: Group I received carbopol 974P NF empty gel, Groups II and III were treated topically with carbopol gel containing 2.5% and 5% of Vitex doniana extract. Group IV received BetadineÂ® 10% as standard drug. The efficacy of treatment was evaluated by planimetry and histological analysis. We secondary used the gel containing Vitex doniana at 2.5% and the pure extract at 10 mg/ml on the model of ear edema induced by xylene. Skin toxicity test was performed with the gel containing Vitex doniana at 5% and the pure extract at 30 mg/ml. Vitex doniana at 5% and 2.5% provided better wound contraction (91.14% and 86.38%) at day 12 post-excision when compared to control (51.15%). The results of histological evaluation supported the outcome of excision wound model. Moreover Vitex doniana inhibited significantly edema induced by xylene when compared to control (p< 0.05). In skin toxicity test, no abnormal symptoms were developed over 14 day-time period. Vitex doniana inhibits the topical inflammation and accelerate cutaneous wound repair.